Электрические характеристики тлеющего разряда в воздухе над поверхностью раствора сульфата алюминия в воде - Шуаібов Олександр; Чучман Михайло; Месарош Лівіа; Alexander Shuaibov; Mikhailo Chuchman; Livia Mesarosh; Mészáros Lívia (Институт прикладной физики (Institutul de Fizică Aplicată), 2017)
Abstract. The paper presents the current-voltage characteristics of the magnitude of the cathode potential drop, the dependencies of the full and specific power pumped into plasma on the density of electrons depending on the current for the glow discharge in air at atmospheric pressure with the cathode on the base of 1–10% solution of aluminum sulfate in distilled water. The distance from the electrolytic liquid cathode to the metal anode varied in the range of 1–10 mm, at an average discharge current of 8–36 mA. The discharge is promising for the synthesis of nanostructures of aluminum and aluminum oxide which are formed due to processing of the solutions by glow discharge.

Резюме. Приведены вольт-амперные характеристики, величины катодного падения потенциала, зависимости полной и удельной мощности тлеющего разряда, которая вкладывалась в плазму от величины тока разряда, а также плотность электронов в тлеющем разряде в воздухе атмосферного давления с катодом на основе 1–10-процентных растворов сульфата алюминия в дистиллированной воде. Расстояние от жидкого электролитического катода до металлического анода варьировалось в диапазоне 1–10 мм при среднем токе разряда 8–36 мА. Разряд перспективный для синтеза наноструктур из алюминия и его оксида, которые образуются вследствие обработки растворов тлеющим разрядом.
Electrical characteristics of a glow discharge in air over the surface of aluminum sulfate aqueous solution
Keywords: тлеющий разряд с жидким катодом; электрические характеристики; glow discharge with liquid cathode; electrical characteristics